The Effect of IDO on Neural Progenitor Cell Survival Under Oxygen Glucose Deprivation - Wang, Jixian; Wang, Brian; Jiang, Lei; Zhou, Kaijing; Yang, Guo-Yuan; Jin, Kunlin (Frontiers in Cellular Neuroscience, 2020)
Objective: Indoleamine-2,3-dioxygenase (IDO) activity plays an important role in many neurological disorders in central nervous system, which may associate with immunomodulation or anti-inﬂammatory activity. However, the action of IDO in ischemic condition is still poorly understood. The purpose of present study is to explore the expression and action of IDO in stem cell culture under oxygen and glucose deprivation. Methods: Neural progenitor cells were obtained from the human embryonic stem cell line BG01. These cells underwent oxygen and glucose deprivation. We examined the IDO expression at 3 and 8 hours of oxygen and glucose deprivation and then examined neuronal progenitor cell viability in the normal and oxygen and glucose deprivation condition using the [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assay. In addition, we studied the effect of IDO inhibition and the expression of TNF-, IGF-1, VEGF, IL-6, FGF, TGF,EGF, and Leptin to explore the mechanism of IDO under the oxygen and glucose deprivation. Results: IDO expression in neural progenitor cells increased under oxygen and glucose deprivation, which is closely associated with cell death (p<0.05). Inhibiting IDO did not affect cell survival in normal neural progenitor cells. However, inhibiting IDO could attenuate cell viability under oxygen and glucose deprivation (p<0.05). Further study demonstrated that IDO expression was closely associated to the growth factors leptin expression. Conclusions: Our results demonstrated that increase of IDO under oxygen and glucose deprivation was associated with cell death, suggesting inhibiting IDO could be a target for the neuroprotection.